2011
DOI: 10.1007/s10967-011-1390-6
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian method with empirically fitted priors for the evaluation of environmental radioactivity: application to low-level radioxenon measurements

Abstract: To cite this version:Isabelle Rivals, Clément Fabbri, Guillaume Euvrard, Xavier Blanchard. A Bayesian method with empirically fitted priors for the evaluation of environmental radioactivity: application to low-level radioxenon measurements. Journal of Radioanalytical and Nuclear Chemistry, Springer Verlag, 2012, 292 (1) Corresponding author: Isabelle RivalsAbstract The decision that a given detection level corresponds to the effective presence of a radionuclide is still widely made on the basis of a classic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Such results paved the way to an implementation of the Bayesian approach for xenon detection. Rivals et al (2012) [13] developed a Bayesian method using specific priors for the detection of radioxenon isotopes in noble gas measurement stations of the International Monitoring System (also related to the Comprehensive Nuclear-Test-Ban Treaty Organization). Results showed that the detection capability benefited from the estimation of the radioactivity prior density probability, the confidence interval for the true radioactivity level, and the probability of no radioactivity being present.…”
Section: Related Workmentioning
confidence: 99%
“…Such results paved the way to an implementation of the Bayesian approach for xenon detection. Rivals et al (2012) [13] developed a Bayesian method using specific priors for the detection of radioxenon isotopes in noble gas measurement stations of the International Monitoring System (also related to the Comprehensive Nuclear-Test-Ban Treaty Organization). Results showed that the detection capability benefited from the estimation of the radioactivity prior density probability, the confidence interval for the true radioactivity level, and the probability of no radioactivity being present.…”
Section: Related Workmentioning
confidence: 99%